Assassination Classroom: Time to Go to School - Vol 19 - Matsui, Yusei (Viz Media San Francisco, CA, 2017)
So how are you going to pull off the killing of your teacher (the best one you ever had)? You got an "F" on your quiz and he mispronounced your name again!!! Can your classmates help or are they too pathetic?
Keywords: Extraterrestrials; Junior high students; Graphic novel